(untitled) (El-Wahat Journal for Research and Studies, 2023)
Abstract: This study aimed to evaluate depressive symptoms in 56 women exposed to marital violence and to explore their distribution according to socioeconomic variables and types of marital violence. Depressive symptoms were assessed using Beck Depression Inventory (BDI)-II. Semi-structured interview was used to collect information about socio-demographics characteristics, types of violence experienced and the onset of marital violence. Findings showed that 58.92% of the women of our sample were severely depressed. Furthermore, the severity of depression symptoms was higher in women who experienced both physical and psychological violence, housewives and women with a high school level. Those results emphasize the impact of marital violence as a risk factor for depression. Keywords: Depressive symptoms, Depression, Marital violence, Women, Algeria. ملخص : هدفت هذه الدراسة الى تقييم الأعراض الاكتئابية عند 56 امرأة ضحية العنف الزوجي و استقصاء توزيعهم وفق المتغيرات السوسيوديموغرافية و أنواع العنف الزوجي. تم تقييم الأعراض الاكتئابية باستعمال قائمة بيك الثانية للاكتئاب. تم استعمال مقابلة نصف موجهة بهدف الحصول على الخصائص السوسيوديموغرافية و أنواع العنف الزوجي المتعرض له. أظهرت النتائج ان 58.92 بالمائة من نساء عينتنا تعرضن لاكتئاب شديد. بالإضافة الى ذلك كانت حدة الأعراض الاكتئابية أعلى عند النساء اللائي تعرضن الى العنف الجسدي و النفسي معا و النساء الماكثات في البيت و النساء ذوي مستوى دراسي ثانوي. تشدد هذه الدراسة على تأثير تجربة العنف الزوجي باعتبارها عامل خطر لظهور الاكتئاب. كلمات دالة : الأعراض الاكتئابية, الاكتئاب , عنف زوجي, نساء ,الجزائر